Dinamika Pertumbuhan Ekonomi Regional Sumatera Utara : Integrasi Infrastruktur Jalan Tol dan Kapasitas Modal Manusia: The Dynamics of Regional Economic Growth in North Sumatra : The Integration of Motorway Infrastructure and Human Capital - Choiroel Woestho; Adi Wibowo Noor Fikri; Zian Fachrian (OGZ Research & Publishing, 2026)
Objective: This study aims to evaluate the impact of policy on regional economic growth using a Difference-in-Differences (DID) approach with a Random-Effects GLS model. Methods: Methods Using panel data from 33 regions. This study analyses the effectiveness of the intervention by controlling for the Human Development Index (HDI), local fiscal capacity, and the share of the manufacturing and trade sectors. The estimation results indicate that the model has strong validity, with a Prob > chi2 value of 0.0000. Research Results: The findings show that economic growth increased by 4.03% after the policy intervention across all observed regions. However, the DID interaction coefficient of 0.0127 indicates that the policy did not produce a statistically significant difference between the treatment and control groups (p = 0.405). In addition, the Human Development Index (HDI) and fiscal capacity showed marginal and insignificant effects, suggesting that regional economic growth remains influenced by broader macroeconomic factors and overall time trends. Therefore, infrastructure policies need to be integrated with the real sector and local economic empowerment to generate stronger short-term impacts.